Renal denervation in patients with end-stage renal disease and resistant hypertension on long-term haemodialysis. Issue 5 (May 2020) - Scalise, Filippo; Sole, Andrea; Singh, Gurbhej; Sorropago, Antonio; Sorropago, Giovanni; Ballabeni, Cinzia; Maccario, Massimo; Vettoretti, Simone; Grassi, Guido; Mancia, Giuseppe
Abstract : Introduction: Recent randomized controlled trials have confirmed the ability of renal denervation to lower blood pressure (BP) in patients, resistant to the BP-lowering effect of multiple antihypertensive drug administration. Evidence is limited, however, in patients with end-stage renal disease (ESRD) and haemodialysis, a condition in which a persistent BP elevation, despite administration of many antihypertensive drugs, is common. Aim of the present study was to test the BP-lowering efficacy of renal denervation in patients with resistant hypertension and ESRD on haemodialysis. BP was measured repeatedly in the office and over the 24 h during 1-year follow-up. Methods and results: The study was conducted from February 2017 to January 2018 at the Policlinico of Monza, Monza, Italy. We included 24 men and women aged at least 20 years (mean 55 ± 16) who had ESRD, were on long-term haemodialysis and exhibited resistant hypertension, that is, elevated office and ambulatory BP values, despite multidrug antihypertensive treatment ( n = 5.4 ± 1). We excluded patients with renal artery stenosis, malignancy, and a probable life expectancy less than 1 year. Twelve patients were included in the renal denervation and 12 in the medical treatment (control) group. All patients underwent office and 24 h ambulatory BP measurements at baseline and at 1, 6 and 12 months during the follow-up. In the renal denervation group, baseline office and 24 h mean SBP were 180 ± 112 and 175 ± 11 mmHg, respectively, the corresponding values in the control group being 181 ± 19 and 181 ± 20 mmHg. Most of the other baseline characteristics were also similar or only slightly different between groups, including the mean number of administered antihypertensive drugs at baseline. SBP showed an early and persistent reduction after renal denervation (office SBP: 165 ± 13; 150 ± 7 and 149 ± 11mmHg; 24 h SBP 163 ± 20, 148 ± 10 and 149 ± 17 mmHg after 1, 6 and 12 months, respectively). The BP-lowering effect was almost always present and statistically significant during both the day and night. DBP changes followed a similar pattern whereas heart rate never showed any significant change. No significant periprocedural complication of renal denervation was seen. The mean number of administered drugs did not show any significant BP change during the study. Conclusion: In ESRD patients under long-term haemodialysis in whom BP was markedly elevated despite administration of many antihypertensive drugs, renal denervation lowered both ambulatory and office BP. The reduction persisted over a 1-year follow-up. Abstract : Supplemental Digital Content is available in the text